Photochemically induced cyclic morphological dynamics via degradation of autonomously produced, self-assembled polymer vesicles - Chenyu Lin (Nature Portfolio, 2021)
Polymerisation induced self assembly can lead to unusual morphology and dynamics of resultant structures. Here the mechanism of the collective dynamics of a self-assembled polymer system under light irradiation, including self-replication, is eludicated.